2020
DOI: 10.3390/cells9030644
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastomas Exhibit Stem Cell Potential, Possess Neurotrophic Properties, and Establish Connections with Trigeminal Neurons

Abstract: Ameloblastomas are locally invasive and aggressive odontogenic tumors treated via surgical resection, which results in facial deformity and significant morbidity. Few studies have addressed the cellular and molecular events of ameloblastoma onset and progression, thus hampering the development of non-invasive therapeutic approaches. Tumorigenesis is driven by a plethora of factors, among which innervation has been long neglected. Recent findings have shown that innervation directly promotes tumor progression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 86 publications
(156 reference statements)
2
17
0
Order By: Relevance
“…Ameloblastoma cells can also express markers of dental epithelial stem cells (i.e. SOX2 and BMI1), and therefore, they have the potential to transdifferentiate into cancer stem cells and subsequently be responsible for tumor relapse [ 27 ]. The fragmentation of primary tumors during conservative surgical procedures resulting in the seeding of ameloblastoma cells on wound beds may also contribute to increasing the recurrence risk [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ameloblastoma cells can also express markers of dental epithelial stem cells (i.e. SOX2 and BMI1), and therefore, they have the potential to transdifferentiate into cancer stem cells and subsequently be responsible for tumor relapse [ 27 ]. The fragmentation of primary tumors during conservative surgical procedures resulting in the seeding of ameloblastoma cells on wound beds may also contribute to increasing the recurrence risk [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…" 24 Accordingly, at appropriate levels of expression, it generates a cellular state that can respond to microenvironmental needs, thus conferring SOX2‐expressing cells the ability to differentiate downwards defined lineages, mostly of neural differentiation 25 . In this context, it has been shown that the stromal cells in AMB expressing P75NTR, 3 another stem cell marker also related to neural differentiation, together with stromal fibroblasts expressing the stem cell marker CD90, may affect the aggressiveness of this tumor 26 . An additional level of action of SOX2 is promotion of tumor aggressiveness and the process of epithelial‑mesenchymal transition (EMT) in several types of cancers, like in tongue squamous cell carcinoma 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells confer tissues the potential for repair and regeneration and also tumorigenic properties 1 . Apparently, dental tissues 2 and related lesions 3 are not an exception. Octamer‐binding transcription factor 4 (Oct4), Nanog, and sex‐determining‐region‐Y‐box2 (SOX2) are considered as core transcription factors necessary for pluripotency in embryonal stem cells and are known to act as either transcriptional activators or repressors and share a substantial fraction of their target genes 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Co-cultures of trigeminal ganglia with embryonic and postnatal teeth in microfluidic chips faithfully reproduced the in vivo situation, for example innervation was constantly repealed over several days of culture by embryonic teeth, while it was promoted and attracted by postnatal teeth (Pagella et al, 2014b). Then, this chip was employed to study the neurotrophic properties of ameloblastomas (Pagella et al, 2020a) as well as to compare the neurotrophic properties of hDPSCs and human bone marrow stem cells, showing that www.ecmjournal.org hDPSCs induce the growth of significantly longer axons as well as the formation of extensive neuronal networks (Pagella et al, 2020b). In this case, narrow grooves between the channels allow only axons to pass and establish a connection between the compartments (Fig.…”
Section: Microfluidic Devices For the Emulation Of Human Dental Tissuesmentioning
confidence: 93%